Novel MOF catalysts based on calix[4]arene for the synthesis of propylene carbonate from propylene oxide and CO2. (December 2022) - Isaeva, Vera I.; Timofeeva, Maria N.; Lukoyanov, Ivan A.; Gerasimov, Evgeny Yu.; Panchenko, Valentina N.; Chernyshev, Vladimir V.; Glukhov, Lev M.; Kustov, Leonid M.
Abstract: In this study, novel composite materials based on calix[4]arene with hydroxyl groups in the arene "bowl" (K-OH) and the aluminum(III) 2-aminoterephthalate metal organic framework (NH2 -MIL-101(Al), MIL) have been synthesized according to in situ or " bottle around ship " strategy. The effect of the synthesis method, i.e., MW-assisted technique (MW) and the solvothermal procedure (Solv), on the structural, morphological, textural and catalytic properties of MIL/K-OH composites was demonstrated. Catalytic performance of the MIL/K-OH(MW) and MIL/K-OH(Solv) composites was studied in solvent-free coupling of CO2 and propylene oxide (PO) to produce propylene carbonate (PC) at 0.8 MPa of CO2 and 80 °C. The activity of the MIL/K-OH(Solv) catalyst was higher in comparison with MIL/K-OH(MW) material as a result of the differences in the textural properties. The binary system MIL/K-OH(MW)/[n-Bu4 N]Br was demonstrated to be a promising catalyst for cycloaddition of CO2 to PO. In its presence, the conversion of PO was 77 % with 99 % selectivity towards PC at 1.2 MPa of CO2, 50 °C for 24 h. Highlights: Composites based on calix[4]arene with OH groups and NH2 -MIL-101(Al), MIL. MW-synthesis and solvothermal procedure affect the structure and catalytic properties of composites. Solvent-free coupling of CO2 and propylene oxide to produce propylene carbonate. The conversion of propylene oxide was 77 % with 99 % selectivity to propylene carbonate.